1997
DOI: 10.1287/mksc.16.4.295
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Waiting Time Guarantees on Customers' Waiting Experiences

Abstract: Customers often have to wait during the process of acquiring and consuming many products and services. These waiting experiences are typically negative and have been known to affect customers' overall satisfaction with the product or service. To better manage these waiting experiences, many firms have instituted a variety of programs not only to reduce the actual duration of the wait but also to improve customers' perceptions of it. In this paper, we examine the impact of one such initiative, namely, the insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(111 citation statements)
references
References 21 publications
4
103
0
4
Order By: Relevance
“…Taylor (1994) shows that delays affect customers' overall service evaluations. Hui and Tse (1996) and Kumar et al (1997) There is a substantial literature on queues with impatient customers. Models with balking and reneging (leaving after waiting for some time) can be found in many books, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor (1994) shows that delays affect customers' overall service evaluations. Hui and Tse (1996) and Kumar et al (1997) There is a substantial literature on queues with impatient customers. Models with balking and reneging (leaving after waiting for some time) can be found in many books, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that customers tend to be relatively dissatisfied with long waiting time compared with short waiting time generally (Taylor, 1994;Lee et al, 2012;Lin et al, 2015). Customers also tend to be dissatisfied with waiting duration for service delivery where they are uncertain about waiting time, when they do nothing during waiting, when they are with a group, when there are no explanations, apology or compensations for perceived unacceptable waiting durations (Bae and Kim, 2014;Antonides et al, 2002;Kumar et al, 1997). Customer satisfaction with waiting time can affect their post-purchase decisions such as repeated patronage, recommendation of service provider and loyalty to service provider (Abbasi et al, 2013;Lerclec et al, 1995;Lin et al, 2015;Palawatta, 2015).…”
Section: Waiting Time Satisfaction (Wts)mentioning
confidence: 99%
“…Waiting time guarantees are a kind of commitment from a service provider to serve its customers within a specified period of time. If a firm fails to meet this commitment for some customers then it compensates them for the delay (Kumar et al, 1997). Kumar et al, (1997) offered their participants waiting-time guarantees.…”
Section: Compensation For Waiting (Cmp) and Waiting Time Satisfactionmentioning
confidence: 99%
“…Spreng & Olshavsky (1996) conclude the satisfying feeling comes from the comparison of perceived performance with consumer's internal desire and expectation to the service or product. Several studies indicated that customer satisfaction is not only the evaluation of post purchasing, but also accompanying consumer's behavioral intentions, such as customer loyalty, word of mouth communication (Hart & Rosenberger III, 2004;Kumar, Kalwani, & Dada, 1997). The satisfaction used in current study was adopted the concept that consumers would evaluate the expectation of product or service according to their consumption experiences.…”
Section: Effect Of Perceived Valuementioning
confidence: 99%